2014
DOI: 10.1007/s40474-014-0020-8
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Spectrum Disorders: Recent Neuroimaging Findings

Abstract: Since the identification of Fetal Alcohol Syndrome over 40 years ago, much has been learned about the detrimental effects of prenatal alcohol exposure on the developing brain. This review highlights recent neuroimaging studies, within the context of previous work. Structural magnetic resonance imaging has described morphological differences in the brain and their relationships to cognitive deficits and measures of facial dysmorphology. Diffusion tensor imaging has elaborated on the relationship between white m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 76 publications
(88 reference statements)
6
66
0
1
Order By: Relevance
“…For individuals with a history of PAE, considerable effort has been devoted to understanding the neural bases of the learning and behavioral deficits seen in these children with considerable evidence supporting the adverse impact on the size, cytoarchitecture, function, and connectivity of the brain (Ashwell et al, 1996, Coles et al, 2011, Lebel et al, 2011, Moore et al, 2014, Wilhelm et al, 2015). The results of this study indicated that utilization of oxygen in the PFC to modulate arousal was altered as a function of PAE, which may indicate damage to neural tissue of the PFC or disruption to the connectivty of the neural tissue in this area resulting in disruption to oxygen utilization.…”
Section: Discussionmentioning
confidence: 99%
“…For individuals with a history of PAE, considerable effort has been devoted to understanding the neural bases of the learning and behavioral deficits seen in these children with considerable evidence supporting the adverse impact on the size, cytoarchitecture, function, and connectivity of the brain (Ashwell et al, 1996, Coles et al, 2011, Lebel et al, 2011, Moore et al, 2014, Wilhelm et al, 2015). The results of this study indicated that utilization of oxygen in the PFC to modulate arousal was altered as a function of PAE, which may indicate damage to neural tissue of the PFC or disruption to the connectivty of the neural tissue in this area resulting in disruption to oxygen utilization.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of fMRI studies in FASD have focused on the detection of brain activation associated with different cognitive functions (for review, see Moore, Migliorini, Infante, & Riley, 2014). Building on this technique, examining task-based functional connectivity may be an important step towards understanding local changes in brain activity during performance of a task by exploring the neural network in which information is shared and integrated in response to different cognitive processes (Ernst, Torrisi, Balderston, Grillon, & Hale, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research data support the presence of changes to both structural and functional integrity of the brain [18,19] in individuals with PAE. Consistent with the extensive data on the mechanisms of alcohol as a potent neurobehavioral teratogen [20], these alterations can result in a range of neurodevelopmental outcomes with wide individual variation.…”
Section: Diagnostic Featuresmentioning
confidence: 90%